1992
DOI: 10.1093/intimm/4.8.935
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of human anti-mouse H-2E xenorecognition: T cell receptor bias and impaired CD4 interaction contribute to weak xenoresponses

Abstract: T lymphocyte responses to the MHC of an evolutionarily distant species are known to be weak compared with responses against allogeneic MHC products within a species. This fact was used to examine the regions of human MHC class II molecules required for the stimulation of strong primary immune responses against MHC alloantigens. A panel of mouse DAP.3 transfectants expressing the products of wild-type and recombinant DR1/H-2Ek MHC class II genes paired to either DR alpha or H-2E alpha genes was generated, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This raised the possibility that CD4 may stabilize the 'dimer of dimers' and promote the aggregation of TcRs on the surface of the activating T-cell, especially if CD4 itself has a propensity to dimerize [75, 761. It was evident from domain shuffling data [69], CD4 mutagenesis [63,[77][78][79][80][81][82] and antibody binding studies [62, 64, 831 that more than one region within the CD4 molecule is involved in class I1 binding. The data described in this section exploit the species barrier between mouse class I1 molecules and human CD4 [67][68][69]841 to study the role of the a2 domain in T-cell recognition by introducing the a2 domain of murine H-2E into HLA-DR1. It has been shown that the a2 domain appears to contribute to T-cell recognition, and we believe that the most likely explanation for this is that it has a role in CD4 binding, particularly in the light of subsequent mutagenesis data [85].…”
Section: Contribution Of the Class II Az Domain To T-cell Recognitionmentioning
confidence: 99%
“…This raised the possibility that CD4 may stabilize the 'dimer of dimers' and promote the aggregation of TcRs on the surface of the activating T-cell, especially if CD4 itself has a propensity to dimerize [75, 761. It was evident from domain shuffling data [69], CD4 mutagenesis [63,[77][78][79][80][81][82] and antibody binding studies [62, 64, 831 that more than one region within the CD4 molecule is involved in class I1 binding. The data described in this section exploit the species barrier between mouse class I1 molecules and human CD4 [67][68][69]841 to study the role of the a2 domain in T-cell recognition by introducing the a2 domain of murine H-2E into HLA-DR1. It has been shown that the a2 domain appears to contribute to T-cell recognition, and we believe that the most likely explanation for this is that it has a role in CD4 binding, particularly in the light of subsequent mutagenesis data [85].…”
Section: Contribution Of the Class II Az Domain To T-cell Recognitionmentioning
confidence: 99%